2020
DOI: 10.3390/cells9092021
|View full text |Cite
|
Sign up to set email alerts
|

Novel Opportunities for Cathepsin S Inhibitors in Cancer Immunotherapy by Nanocarrier-Mediated Delivery

Abstract: Cathepsin S (CatS) is a secreted cysteine protease that cleaves certain extracellular matrix proteins, regulates antigen presentation in antigen-presenting cells (APC), and promotes M2-type macrophage and dendritic cell polarization. CatS is overexpressed in many solid cancers, and overall, it appears to promote an immune-suppressive and tumor-promoting microenvironment. While most data suggest that CatS inhibition or knockdown promotes anti-cancer immunity, cell-specific inhibition, especially in myeloid cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 114 publications
(170 reference statements)
1
22
0
Order By: Relevance
“…Ctss is a cysteine protease expressed by diverse immune cells that is responsible for cleaving certain extracellular matrix proteins and cell adhesion molecules to pro-mote immune cell motility [66,67]. In the acute phase after TBI, the upregulation of Ctss expression was mainly observed in microglia; inhibiting Ctss could reduce the level of inflammatory factors, alleviate brain edema, and improve neurobehavioral function [68].…”
Section: Discussionmentioning
confidence: 99%
“…Ctss is a cysteine protease expressed by diverse immune cells that is responsible for cleaving certain extracellular matrix proteins and cell adhesion molecules to pro-mote immune cell motility [66,67]. In the acute phase after TBI, the upregulation of Ctss expression was mainly observed in microglia; inhibiting Ctss could reduce the level of inflammatory factors, alleviate brain edema, and improve neurobehavioral function [68].…”
Section: Discussionmentioning
confidence: 99%
“…The ethanol extract of C. monogyna produced a dose-dependent inhibition of cathepsin S, with a 71.7% maximum inhibition of enzyme activity. Although cathepsin inhibitors, including inhibitors of cathepsin S, have been extensively studied for their anti-inflammatory and anti-cancer properties, very few researchers have investigated medicinal plants used in the treatment of cardiovascular disease for cathepsin S inhibition [25,26]. As one of the few studies on plant extracts or compounds as cathepsin S inhibitors, Hsin et al [27] reported that hispolon isolated from Phellinus igniarius mediated the downregulation of cathepsin S expression and inhibited cell metastasis in cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine cathepsin proteases are degradative enzymes that are involved in lysosomal functions such as protein degradation, autophagy, and cell death. These enzymes are also involved in the features of malignant transformation, including altered adhesion, dysregulated degradation of the ECM, invasion into the vasculature, and distant metastasis [ 30 , 31 ]. CTSD is an aspartic endo-protease that ubiquitously distributed in lysosomes.…”
Section: Discussionmentioning
confidence: 99%